AB0914 BONE LOSS AND NEW FRACTURES WITH DENOSUMAB TREATMENT. (2nd June 2020) - Sanguesa, C.; Casafont-Solé, I.; Nack, A.; Holgado Pérez, S.; Martínez-Morillo, M.; Aparicio Rovira, M.; Prior-Español, Á.; Aparicio Espinar, M.; Riveros, A.; Mateo, L.; Olive, A.; Gifre, L.
Abstract : Background: The incidence and factors related to an inadequate response to denosumab (Dmab) treatment remain unclear. Objectives: To describe clinical, analytical and densitometric characteristics of patients with inadequate response (IR) to Dmab in clinical practice. IR was defined as the presence of a new fracture [fxs-IR] or a significant decrease in BMD (≥5% lumbar or ≥4% femoral) [BMD-IR]. Methods: retrospective study of patients with IR to Dmab treatment. Data of demographic variables, risk factors for osteoporosis, history of fractures, previous anti-osteoporotic treatment, densitometric and analytical parameters were collected before and after IR. Results: 22 patients were included (19W:3M) with mean age of 75±10years. The causes of osteoporosis were: postmenopausal (50%), induced by glucocorticoids (22.7%), alcoholic (9.09%) and multifactorial (18.8%). Most patients were previously treated with bisphosphonates (59.09%, duration 5.2±2.6y) and had previous vertebral fractures (54.54% %, median 3). During Dmab treatment, 10 patients presented a BMD-IR (with a mean bone loss up to -3.5% at femur and -5.8% at lumbar spine) and 12 had fxs-IR (vertebral [n=8], humerus [n=1], pelvis [n=1], tibia [n=1]). No significant differences were observed in duration of Dmab between both IR groups (Fxs-IR: 3, 2±1, 9 vs BMD-IR: 2, 4 ± 1, 2y). In the BMD-IR, the BMD loss was higher at lumbar spine than at total hip (-6.6%±3.7 vs -1.9%±4.8). Only 1 patient of the fxs-IR had a secondary cause of IR (mieloma multiple). In the fxs-IR group, most patients started combined treatment with teriparatide (n=4), 1 changed to teriparatide and 7 remained with Dmab. In the BMD-IR group, most mantained Dmab treatment (n=8) and 2 switched to zoledronate. Conclusion: Most patients who developed IR to Dmab had been previously treated with bisphosphonates and had previous fragility fractures and appears within the first 3 years of treatment. BMD loss seems to be more marked at spine than total hip. Only one patient had a secundary cause of IR. Disclosure of Interests: None declared